Prognostic value of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) in patients with RAS-mutant metastatic colorectal cancer - Xie, Wenxia; Liu, Huizhuo; Shi, Yunjiao; Zhang, Bingxin; Wang, Ruoyun; Wang, Shayan; Liang, Bin (Frontiers in Nutrition, 2025)
BackgroundPatients with metastatic colorectal cancer (mCRC) generally have a poor prognosis, and treatment strategies are highly dependent on the RAS mutational status. During disease progression, patients often exhibit dynamic changes in serum lipid profiles. However, the prognostic significance of cholesterol-related biomarkers remains controversial. This study aimed to investigate the association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and clinical outcomes in patients with RAS-mutant mCRC.MethodsThis retrospective study included 287 RAS-mutant mCRC patients, all of whom received at least three cycles of chemotherapy combined with bevacizumab. Among them, 169 patients were assigned to the training cohort and 118 patients to the validation cohort. Pearson's correlation coefficient and Spearman's rank correlation test were used to assess the relationships between continuous variables. The optimal cutoff value for the NHHR was determined using the maximum selection rank statistic, categorizing patients into high and low NHHR groups. Kaplan-Meier survival curves were used to assess survival in the high and low NHHR groups, with differences between groups compared using the log-rank test. Restricted cubic splines (RCS) were employed to analyze the non-linear relationship between NHHR and mortality risk. Univariate and multivariate Cox regression models were used to assess the independence of NHHR in predicting survival outcomes, with stepwise adjustment for confounders and stratified analysis. A nomogram was constructed based on the final model.ResultsAfter adjusting for confounders, the high NHHR group (>3.45) had a significantly higher mortality risk than the low NHHR group (HR = 2.23, 95% CI: 1.46–3.40, P < 0.001). Subgroup analyses revealed a stronger association in female patients (female, HR = 4.24, 95% CI: 1.85–9.71; male, HR = 1.72, 95% CI: 1.09–2.73; P for interaction = 0.037). The RCS analysis showed a linear increase in mortality risk with increasing NHHR (P for overall P < 0.001, P for non-linearity = 0.090). NHHR showed significant positive correlations with white blood cells, monocytes, neutrophils, fibrinogen, CA199, and CEA (all P < 0.05), and significant negative correlations with albumin, sodium, and chloride (all P < 0.05). The nomogram demonstrated robust predictive performance.ConclusionNHHR may serve as a potential prognostic biomarker in patients with RAS-mutant metastatic colorectal cancer. Its putative role in promoting tumor progression through modulation of chronic inflammation warrants further investigation.